'Vigilante Shows' and Law Enforcement in Russia. Issue 1 (2nd January 2021) - Favarel-Garrigues, Gilles
Abstract: Moral entrepreneurs who volunteer to enforce rules by themselves have spread in 2010s Russia. As 'rule enforcers' they patrol the streets to catch offenders. Some of these enforcers have conflictual relations with the police, while others operate in cooperation with it. This essay describes the development of vigilante justice in contemporary Russia. Two particularities of the Russian case are striking. First, the activities of several citizen policing initiatives are in fact recorded and posted on YouTube and VKontakte, where they reach a large audience, generating support for their activities and, in particular, for the leaders of such groups. Second, the development of these groups is not the simple outcome of a powerless state failing to maintain order or to fight crime. The essay will reveal how these new forms of policing contribute, paradoxically, to the strengthening of state authority.